How Consistency, Reviews, And Ratings Shape Seller Reputation: Customer Experience Mediation on Shopee - Farida, Noor; Lusianti, Dina; Soegiarto, Dwi (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Objective – This study examines how Consistency, online reviews, and ratings influence seller reputation, with customer experience as a mediating mechanism in the Shopee marketplace. Design/methodology/approach – A quantitative approach was employed, using questionnaire data from Shopee users, with up to 252 respondents. The proposed model was tested using PLS-SEM (SmartPLS) to evaluate direct and indirect relationships among constructs. Findings – Consistency positively influences customer experience and seller reputation. Ratings positively affect customer experience and seller reputation and are the strongest direct drivers of reputation. Customer experience positively affects seller reputation. Online reviews positively influence seller reputation but do not significantly affect customer experience. Customer experience mediates the effects of consistency and ratings on seller reputation, whereas mediation is not supported for online reviews. Research limitations/implications – The findings are based on cross-sectional, self-reported data from a single platform, limiting causal inference and generalizability. Future studies may incorporate longitudinal designs, objective behavioral indicators, and additional review attributes (e.g., valence and credibility). Practical implications – Sellers should prioritize consistent service performance and maintain strong ratings to enhance reputation through improved customer experience. Platforms can strengthen review governance to support reputation formation. Originality/value – This study clarifies how marketplace signals translate into seller reputation directly and through customer experience as an explanatory pathway. Keywords: Consistency, online reviews, ratings, customer experience, seller reputation.